2021
DOI: 10.1093/cid/ciab465
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vaccine Antigen Detected in the Plasma of mRNA-1273 Vaccine Recipients

Abstract: SARS-CoV-2 proteins were measured in longitudinal plasma samples collected from 13 participants who received two doses of mRNA-1273 vaccine. 11 of 13 participants showed detectable levels of SARS-CoV-2 protein as early as day one after first vaccine injection. Clearance of detectable SARS-CoV-2 protein correlated with production of IgG and IgA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(212 citation statements)
references
References 10 publications
8
163
2
1
Order By: Relevance
“…According to the calibration curve in Figure 3, this corresponds to a maximum concentration of 14.6 μg/mL. Recently published work by Ogata et al used a Quanterix assay measured spike protein in the blood at concentrations less than 50 pg/mL on a similar timescale [10]. The large discrepancy between our photonic assay and the Ogata work was intriguing and may reflect the early stage of knowledge in this area.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…According to the calibration curve in Figure 3, this corresponds to a maximum concentration of 14.6 μg/mL. Recently published work by Ogata et al used a Quanterix assay measured spike protein in the blood at concentrations less than 50 pg/mL on a similar timescale [10]. The large discrepancy between our photonic assay and the Ogata work was intriguing and may reflect the early stage of knowledge in this area.…”
Section: Resultsmentioning
confidence: 75%
“…While this was conducted at a relatively high concentration, it is important to know then what sort of concentrations of spike protein exist in the blood of vaccinated subjects and for how long. A recent study determined that SARS-CoV-2 spike protein exists in the blood after vaccination [10]. While this represents a useful first step, additional verification of these data is required, along with the development of a platform that can determine this on a broader scale.…”
Section: Introductionmentioning
confidence: 99%
“…23 The fact that COVID-19 vaccination may induce measurable amount of circulating spike protein, thus playing a possible role in the pathogenesis of VITT, is supported by data published by Ogata and colleagues. 24 Another possible interpretation has been provided by Huynh and colleagues. 25 Briefly, it was first found that the binding of anti-PF4 antibodies in the sera of VITT patients involved eight surface amino acids of PF4, all located within the heparin binding site of the protein, but was different from the antigenic moiety recognized by the anti-PF4 antibodies developing in patients with HITT.…”
Section: Pathogenesis Of Vittmentioning
confidence: 87%
“…These studies highlight CoV-2-S as a potent culprit that could possibly induce systemic inflammation; however, the underlying molecular mechanism is not fully understood. CoV-2-S has two subunits, with its S1 subunit (CoV-2-S1) being able to be shed into blood stream (Ogata et al, 2021), Importantly, in COVID-19 cases, the serum levels of CoV-2-S1 shows higher positive correlation with clinical severity than CoV-2 nucleocapsid protein (Ogata et al, 2020). Here, our data show that CoV-2-S1 interacts with the extracellular LRR domain of TLR4 and activates NF-kB, suggesting that soluble CoV-2-S1 shed by CoV-2 or infected host cells is a TLR4-recognizable alarmin.…”
Section: Discussionmentioning
confidence: 99%